The Adenosine Hypothesis Revisited: Modulation of Coupling between Myocardial Perfusion and Arterial Compliance - Dobson, Geoffrey P.; Arsyad, Aryadi; Letson, Hayley L. (Frontiers in Physiology, 2017)
For over four decades the thoracic aortic ring model has become one of the most widely used methods to study vascular reactivity and electromechanical coupling. A question that is rarely asked, however, is what function does a drug-mediated relaxation (or contraction) of isolated rings serve in the intact system? The physiological significance of adenosine relaxation in large elastic conduit arteries from a wide range of species remains largely unknown. We propose that adenosine relaxation increases aortic compliance in acute stress states and facilitates ventricular-arterial (VA) coupling, and thereby indirectly matches coronary artery perfusion to myocardial energy metabolism. In 1963 Berne argued that adenosine acts as a local negative feedback regulator between oxygen supply and demand in the heart during hypoxic/ischemic stress. The adenosine VA coupling hypothesis extends and enhances Berne's 'adenosine hypothesis' from a local regulatory scheme in the heart to include conduit arterial function. In multicellular organisms, evolution may have selected adenosine, nitric oxide, and other vascular mediators, to modulate VA coupling for optimal transfer of oxygen (and nutrients) from the lung, heart, large conduit arteries, arterioles and capillaries to respiring mitochondria. Finally, a discussion of the potential clinical significance of adenosine modulation of VA coupling is extended to vascular aging and disease, including hypertension, diabetes, obesity, coronary artery disease and heart failure.